Developing an instrument to measure the influential factors on career choice among Iranian nursing students - Shahhosseini, Zohreh (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Understanding why the graduates from the high schools choose nursing is essential for the health policy makers in each country and Iran is not an exception. The aim of this study was to develop an instrument measuring the influential factors on career choice among Iranian nursing students. MATERIALS AND METHODS: This methodological study employed both qualitative and quantitative approaches. In the first phase of the study, the items were generated for the instrument. These items were drawn from a relevant literature review along with taking a poll of experts’ opinions. Then the psychometric properties of instrument were measured using content validity, face validity, and construct (exploratory factor analysis) validity as well as its reliability. RESULTS: Initially, a 35-item instrument was developed. In the second phase, a scale-level content validity index of 0.90 was obtained for the instrument. The factor structure of the inventory was identified by undertaking a principal component analysis in a sample of 139 nursing students. Three factors were extracted with a total variance account of 42.03%. Reliability was demonstrated with Cronbach's alpha coefficient of 0.77 for the entire scale. Consistency of the instrument was established with test — retest reliability with an interval of 2 weeks (intra-cluster correlation = 0.94, P < 0.001). Wilcoxon signed-rank test demonstrated no significant differences between the test — retest scores (P > 0.05). CONCLUSION: It seems a culturally sensitive instrument with a satisfactory level of validity and reliability has some implications for policy makers in nursing education.